[3H]BMT-046091 a potent and selective radioligand to determine AAK1 distribution and target engagement. (15th May 2017) - Louis, Justin V.; Lu, Yifeng; Pieschl, Rick; Tian, Yung; Hong, Yang; Dandapani, Kumaran; Naidu, Sreenivasulu; Vikramadithyan, Reeba K.; Dzierba, Carolyn; Sarvasiddhi, Sarat Kumar; Nara, Susheel J.; Bronson, Joanne; et al.
Abstract: Adaptor-associated kinase 1 (AAK1), a member of the Ark1/Prk1 family of serine/threonine kinases, plays a role in modulating clatherin coated endocytosis of specific surface receptors. We have demonstrated that AAK1 inhibitors are efficacious in rodent models of neuropathic pain (Kostich et al., 2016). Here we have characterized the binding properties and distribution pattern of the tritiated AAK1 radioligand, [ 3 H]BMT-046091, in rodents and cynomolgus monkeys, and used the radioligand to measure the brain target occupancy following systemic administration of AAK1 inhibitors. We have found that [ 3 H]BMT-046091 is potent and selective AAK1 inhibitor. It inhibits AAK1 phosphorylation of a peptide derived from a physiologic substrate, the μ2 subunit of the adaptor protein complex, with an IC50 value of 2.8 nM, and is inactive at >5 μM in a panel of functional or binding assays for receptors, transporters and enzymes. [ 3 H]BMT-046091 binding in the brain is absent in the AAK1 knockout mouse, and is displaceable with a high concentration of AAK1 inhibitors in wild type mice. Specific [ 3 H]BMT-046091 binding is widespread in the brain and spinal cord with the highest density in the cortex, hippocampus, amygdala, striatum and thalamus. In the spinal cord, [ 3 H]BMT-046091 binding appears enriched in the dorsal horn superficial layers. Oral administration of LP-935509, an AAK1 inhibitor, results in a dose-dependent occupation of AAK1 binding sites in the brain and spinal cord. The increase in AAK1 binding site occupancy by LP-935509 correlates with the decrease in antinociceptive responses in the rat chronic constriction injury model of neuropathic pain. Highlights: [ 3 H]BMT-046091 is a potent and selective inhibitor radioligand of AAK1. AAK1 binding sites are widespread in the CNS, and, in the spinal cord, most abundant in the dorsal horn. Ex vivo [ 3 H]BMT-046091 binding autoradiography is successfully used to measure target engagement of AAK1 inhibitors. LP-935509, an AAK1 inhibitor, occupies AAK1 binding sites, and the occupancy correlates with anti-neuropathic pain effects.